Quantification of purified endogenous miRNAs with high sensitivity and specificity - Shin, S; Jung, Y; Uhm, H; Song, M; Son, S; Goo, J; Jeong, C; Song, J-J; Kim, VN; Hohng, S (Springer Nature, 2020)
MicroRNAs (miRNAs) are short (19–24 nt) non-coding RNAs that suppress the expression of protein coding genes at the post-transcriptional level. Differential expression profiles of miRNAs across a range of diseases have emerged as powerful biomarkers, making a reliable yet rapid profiling technique for miRNAs potentially essential in clinics. Here, we report an amplification-free multi-color single-molecule imaging technique that can profile purified endogenous miRNAs with high sensitivity, specificity, and reliability. Compared to previously reported techniques, our technique can discriminate single base mismatches and single-nucleotide 3′-tailing with low false positive rates regardless of their positions on miRNA. By preloading probes in Thermus thermophilus Argonaute (TtAgo), miRNAs detection speed is accelerated by more than 20 times. Finally, by utilizing the well-conserved linearity between single-molecule spot numbers and the target miRNA concentrations, the absolute average copy numbers of endogenous miRNA species in a single cell can be estimated. Thus our technique, Ago-FISH (Argonaute-based Fluorescence In Situ Hybridization), provides a reliable way to accurately profile various endogenous miRNAs on a single miRNA sensing chip.